SUAMI DIPENJARA SEBAGAI ALASAN CERAI GUGAT; PERSPEKTIF FIKIH DAN LEGISLASI NEGERI MUSLIM - Ali Trigiyatno (Arena Hukum, 2021)
AbstractThis paper aims to compare the provisions of fiqh with the legislation in terms of the husband being imprisoned as the reason for the wife to file for divorce in four Muslim countries. They are Indonesia as a representative of the country with the majority of the population following the Shafi'i school, Morocco representing the Maliki school, Jordan representing the Hanafi school, and Qatar representing the Hanbali school. Using a normative approach and a comparative method, this paper aims to look for aspects of similarities as well as differences from fiqh provisions compared to legislation in the four countries. The results shows that the legislation in the four countries basically takes the opinion of the Maliki and Hanbali schools which allow divorce because the husband is imprisoned. From the four countries, Indonesia has set the longest prison term, which is five years, while Morocco and Jordan are imprisoned for a minimum of three years and Qatar is two years. Indonesia and Jordan seem quite far from leaving the rules in the dominant fiqh school in their country by not following the school's fatwa adopted to prohibit divorce because the husband is imprisoned. Meanwhile, Morocco and Qatar are in accordance with the dominant schools of jurisprudence in their countries, with a few additions to more detailed and operational rules.Â AbstrakTulisan ini bertujuan membandingkan ketentuan fikih dengan Undang-undang dalam hal suami dipenjara sebagai alasan istri menggugat cerai di empat negara muslim. Mereka adalah Indonesia sebagai representasi negara dengan mayoritas penduduknya menganut mazhab Syafiâ€™i, Maroko mewakili mazhab Maliki, Yordania mewakili mazhab Hanafi, dan Qatar mewakili mazhab Hanbali. Dengan pendekatan normatif dan metode perbandingan, penulis hendak mencari segi-segi persamaan sekaligus perbedaan dari ketentuan fikih dibanding legislasi di empat negara tersebut. Hasilnya adalah legislasi empat negara pada dasarnya mengambil pendapat mazhab Maliki dan Hanbali yang membolehkan cerai gugat karena suami dipenjara. Dari empat negara, Indonesia menetapkan masa penjara terlama yakni lima tahun, sedang Maroko dan YordaniaÂ dengan batasan minimal dipenjara selama tiga tahun dan Qatar dua tahun. Indonesia dan Yordania terlihat cukup jauh meninggalkan aturan dalam mazhab fikih yang dominan di negaranya dengan tidak mengikuti fatwa mazhab yang dianut untuk melarang cerai gugat karena suami dipenjara. Sementara Maroko dan Qatar masih selaras dengan mazhab fikih dengan sedikit penambahan aturan yang lebih rinci dan operasional.